Protective effect of silymarin on viability, motility and mitochondrial membrane potential of ram sperm treated with sodium arsenite - Farzaneh Eskandari; Hamid Reza Momeni (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2016)
Background: Sodium arsenite can impair male reproductive function by inducing oxidative stress. Silymarin is known as a potent antioxidant. Objective: This study was performed to investigate if silymarin can prevent the adverse effect of sodium arsenite on ram sperm viability, motility and mitochondrial membrane potential. Materials and Methods: Epidydimal spermatozoa obtained from ram were divided into five groups: 1) Spermatozoa at 0 hr, 2) spermatozoa at 180 min (control), 3) spermatozoa treated with sodium arsenite (10 μM) for 180 min, 4) spermatozoa treated with silymarin (20 μM) + sodium arsenite (10 μM) for 180 min and 5) spermatozoa treated with silymarin (20 μM) for 180 min. MTT assay and Rhodamine 123 staining were used to assess sperm viability and mitochondrial membrane potential respectively. Sperm motility was performed according to World Health Organization (WHO) guidelines. Results: Viability (p<0.01), nonprogressive motility (p<0.001) and intact mitochondrial membrane potential (p<0.001) of the spermatozoa were significantly decreased in sodium arsenite treated group compared to control group. In silymarin + sodium arsenite group, silymarin could significantly reverse the adverse effect of sodium arsenite on these sperm parameters compared to sodium arsenite group (p<0.001). In addition, the application of silymarin alone for 180 minutes could significantly increase progressively motile sperm (p<0.001) and decrease non motile sperm (p<0.01) compared to the control. Conclusion: Silymarin could compensate the adverse effect of sodium arsenite on viability, nonprogressive motility and mitochondrial membrane potential of ram sperm.